An Insight Review of Internet of Things (IoT) Protocols, Standards, Platforms, Applications and Security Issues - Ibrahim, Qutaiba; Lazim, Sahar (International Journal of Sensors Wireless Communications and Control, 2021)
Internet of Things is considered a promising and challenging system that needs modern types of protocols and architectures different from conventional networks. This paper aims to provide an inclusive, concise, plain, and precise insight of IoT foundations for the novice and to introduce guidelines for application developers and researchers to be capable of choosing quickly the right protocol at different structural IoT layers and correct hardware/software platform for various applications. The contributions of this review provide the classification for the most widespread suggested IoT architectures. Besides, it summarizes the basic IoT components with their roll into multi-layered architecture. Furthermore, it presents the classification of layers basis for prevalent protocols with the comparison among different protocols at each layer in the IoT domain. Subsequently, IoT applications taxonomy is introduced and the most relevant use-cases are compared. Likewise, at the respective 4- Layer architecture of IoT, the security issues and policies are discussed concisely. Besides, the potential attacks and their countermeasures are tabularized and some of the research challenges with their solutions are identified. Lastly, to ensure that the conducted review is different, the comparison with other relevant reviews and surveys which came out from the last three years is made.
Keywords: hardware platform